Another city? The possible resistance and the resistance effect: A proposal - Rogério Modesto (Fórum Linguístico, 2016)
In this paper we analyze the expression “The city we want” released upon the discursive production of an urban social movement in the city of Salvador, Bahia State, Brazil. The aim of this analysis is the comprehension of the operations we call “possible resistance” and “resistance effect”. In order to do so, we part from Michel Pêcheux’s theoretical reflection regarding the notion of resistance, calling attention for the comprehension of this concept, considering multiple determinations that involve an uncentered subject constituted along with sense, the misconception as the language’s reality and the contradiction as the history’s reality.